Aplicación del sistema de detracciones del impuesto general a las ventas y su incidencia en la situación financiera en B & G Empresas E.I.R.L. de la ciudad de Juanjuí, provincia de Mariscal Cáceres, región San Martín. Año 2013. - Tangoa Morey, Alex (2016)
The tesis, “Applicatión of the general sales tax and its impact on the financial situation in B & G enterprises EIRL Juanjui city, Mariscal Caseres province, San Martin region 2013 “is a research project, its aims to assess how the application of the general system of detractions sales tax affects the financial position of B & G enterprises EIRL Sample of this research consists of B & G enterprises EIRL “is an intentional non probabilistic sample. It is start of applied research because it was not about creating new knowledge but to apply different theories guie the detraction of the IGV system. this research was finished through observation, interviews, library research, the financial statements of B & g enterprises EIRL, applying financial ratios, with the main purpose of determining the incidence of withdrawals of IGV in financial position, in order to propose a restructuring in the tax policies to improve the the way to raise taxes without financially weaken the companies. The system drawdowns IGV has become a useful tool for the collection of taxes, which has ensured the advance payment of tax liabilities of taxpayers, on the other hand has had a negative